Descriptive study of discharge medications in pediatric patients. (June 2020) - Nguyen, Thao T; Bergeron, Erica; Lewis, Teresa V; Miller, Jamie L; Hagemann, Tracy M; Neely, Stephen; Johnson, Peter N
Background: Limited studies have evaluated medications in children discharged from hospitals. Knowledge of the number of medications and dosage forms could provide a baseline to establish a medication discharge prescription program. Objectives: To identify the median number of discharge prescriptions per patient. Secondary objectives included an evaluation of the dosage formulations and frequency, and comparisons of the prevalence of unrounded medication doses between service type (medical vs surgical) and physician provider level (trainees vs attendings). Methods: This retrospective study included children <18 years receiving> 1 discharge prescription during 4 selected months over a 1-year time frame. Comparisons were made via Pearson's chi-square tests, Fisher's Exact tests, and Kruskal–Wallis nonparametric rank tests as appropriate with a priori p value of <0.05. Results: A total of 852 patients were evaluated, with most (78.8%) on a medical service. The median (interquartile range) number of new medications at discharge was 2 (1–3), with the median total number of discharge medications of 3 (2–6). There was no difference in the net change of the median number of home medications stopped and new medications started between service types. The majority (72.2%) received> 1 oral liquid medications. There was no difference in prescribing rates per service type and provider level. There was a difference in the number of unrounded doses between trainees versus attendings, 17.8% versus 9.5%, p  = 0.048. Conclusion: Patients were discharged on a median of three medications, and most received> 1 oral liquid medications. These data can be used to target children who would benefit from medication discharge prescription programs.